Improving Reproductive Health Among Adolescent Girls at SMA 1 Purwakarta Through the Consumption of Turmeric and Red Ginger - Mariska, Ika; Buana, Chalya Calaga (Devotion : Journal of Research and Community Service, 2025)
Adolescent girls often face reproductive health issues such as irregular menstrual cycles and dysmenorrhea. Herbal plants (such as turmeric and red ginger) are known to help balance hormones and reduce menstrual pain.To determine the effect of herbal plant consumption on improving reproductive health among adolescent girls at SMA 1 Purwakarta.A quantitative study using a pretest-posttest one-group design. The sample consisted of 40 adolescent girls selected using purposive sampling. The intervention involved the consumption of herbal drinks made from turmeric and red ginger for 4 weeks. Data were collected through a reproductive health knowledge questionnaire, menstrual cycle records, and the Visual Analog Scale (VAS) for pain intensity. Analysis was performed using a paired t-test.After the intervention, there was a significant increase in reproductive health knowledge (p=0.000), menstrual cycle regularity (p=0.003), and a decrease in menstrual pain intensity (p=0.000). Consumption of herbal plants can be an effective non-pharmacological alternative for improving reproductive health in adolescent girls.